2017
DOI: 10.3892/or.2017.5867
|View full text |Cite
|
Sign up to set email alerts
|

Age at menopause and hormone replacement therapy as risk factors for head and neck and oesophageal cancer

Abstract: There were ~986,000 cases of head and neck cancer (HNC) and oesophageal cancer diagnosed worldwide in 2012. The incidence of these types of cancer is much higher in males than females, although this disparity decreases in the elderly population, suggesting a role for hormones as a risk factor. This systematic review investigates the potential role of female hormones [age at menopause and use of hormone replacement therapy (HRT)] as risk factors for HNC/oesophageal squamous cell carcinoma (SCC). The electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…There are sex differences in the development of esophageal cancer, and women who underwent resection has a higher overall survival rate than men ( 9 ). The known causes (such as smoking, obesity, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are sex differences in the development of esophageal cancer, and women who underwent resection has a higher overall survival rate than men ( 9 ). The known causes (such as smoking, obesity, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Previous report showed that the increased risk of esophageal cancer is related to the decrease in estrogens level ( 6 ). Early menopause increases the risk factors for esophageal squamous cell carcinoma ( 9 ). It has been shown that premenopausal female patients have a prolonged survival than postmenopausal patients and that female ESCC patients with higher serum estradiol level have a favorable survival rate ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that sex hormones, particularly oestrogens, may protect against the development of oesophageal and gastric cancer [16,17]. Several epidemiological studies have investigated the role of hormonal and reproductive factors in the development of oesophageal and gastric cancer risk [18][19][20][21][22]; however, few prospective studies have examined the association between reproductive factors and risk of oesophageal and gastric cancer by subtype and subsite and the published findings are inconsistent [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the impact of marital status on patients is achieved through changes of sex hormones (24)(25)(26), which has often been shown in endocrine diseases, such as thyroid cancer (27), breast cancer, and melanoma (28). A review mentioned that estrogen level was a contributing factor in the pathogenesis of esophageal SCC, and hormone replacement therapy might help reduce the risk of esophageal SCC (29). A prospective cohort study (30) showed that moderate expression of estrogen receptor β (ERβ) was associated with increased survival in patients with gastroesophageal junction cancer.…”
Section: Prognostic Risk Factormentioning
confidence: 99%